Evaluation of mean platelet volume before and after cyclophosphamide treatment in systemic sclerosis associated interstitial lung disease - Atilla, Nurhan; Yıldırım Çetin, Gözde (Journal of Surgery and Medicine, 2020)
Aim: Studies carried out in patients with systemic sclerosis (SSc) have shown that mean platelet volume (MPV) is associated with more advanced stage of SSc. However, the effect of cyclophosphamide (CP) on MPV in systemic sclerosis-associated interstitial lung disease (SSc-ILD) is less clear. In this study, we aimed to investigate the MPV response to CP treatment in SSc-ILD. Methods: Thirty-eight SSc-ILD patients who responded positively to CP were included in this retrospective cohort study. MPV values before the treatment were compared with third, sixth, and ninth months’ values during treatment. Results: Over the nine-year period, 82 patients were diagnosed with SSc in the rheumatology clinic of our hospital. Forty-three of them had SSc-ILD and all were administered CP treatment for 9 months. Thirty-eight clinically benefited from CP, among which 32 were females (84%) and 6 (16%) were males. The MPV levels in SSc-ILD patients after CP (9.44 fL) were significantly higher than those before CP (7.89 fL) (P=0.001). Conclusion: Cyclophosphamide treatment causes an increase in MPV in SSc-ILD. MPV, a negative acute phase reactant, is considered an independent risk factor for coronary and peripheral artery diseases. Patients receiving CP should be followed more closely for such diseases.